Banana Blossom (Musa acuminate Colla) Incorporated Experimental Diets Modulate Serum Cholesterol and Serum Glucose Level in Wistar Rats Fed with Cholesterol. (30th November 2016) - Liyanage, Ruvini; Gunasegaram, Saranya; Visvanathan, Rizliya; Jayathilake, Chathuni; Weththasinghe, Pabodha; Jayawardana, Barana Chaminda; Vidanarachchi, Janak Kamil
Abstract : Hypocholesterolaemic and hypoglycaemic effect of banana blossom were studied in high-cholesterol fed rats. Experimental groups were fed for 4 weeks, with casein as the basal diet (CN), in comparison with two diets containing 0.5% cholesterol (CD) and 0.5% cholesterol + 21% banana blossom powder (CDB). Serum total cholesterol, non-HDL-cholesterol level, and serum glucose concentrations were lower in CDB fed group compared with CD fed group. Lower serum cholesterol and glucose level (P < 0.05 ) in CDB fed group were followed by higher faecal weight, caecal weight, caecal Lactobacilli, and Bifidobacteria population in CDB fed group compared to CD diet fed group. Lower serum AST level in banana blossom fed rats showed the reduction in oxidative stress induced by high cholesterol diet. Based on these data, it could be speculated that banana blossom incorporated experimental diets may modulate the hypocholesterolaemic and hypoglycaemic responses in Wistar rats.